Correlation of Plasma Protein C Levels with Cardiovascular Risk Factors in Middle-Aged Adults: The Atherosclerosis Risk in Communities (ARIC) Study - Conlan, Maureen G; Folsom, Aaron R; Finch, Andrea; Davis, C E; Sorlie, Paul; Wu, Kenneth K; For the ARIC Study Investigators (Thrombosis and Haemostasis, 1993)
To evaluate the association of plasma protein C levels with constitutional, socioeconomic, life-style and biochemical factors important in cardiovascular diseases, we measured protein C levels in 12,290 middle aged (45-64 years) subjects participating in the ARIC study. Protein C levels had a normal distribution with a mean value of 3.17 fig/ml. They were higher in women than men and in whites than blacks; higher in postmenopausal women and further increased by hormonal supplements. The age influence was inconsistent and was considered to be inconsequential. Protein C levels were positively correlated with body mass index, LDL-cholesterol, HDL-cholesterol, and triglycerides and negatively associated with cigarette smoking. These factors should be taken into consideration when establishing normal protein C levels and when analyzing the relation between protein C and arterial and venous thrombotic disorders.